Differential micropollutants bioaccumulation in European hake and their parasites Anisakis sp. (October 2020) - Mille, Tiphaine; Soulier, Laurent; Caill-Milly, Nathalie; Cresson, Pierre; Morandeau, Gilles; Monperrus, Mathilde
Abstract: Organisms are exposed to various stressors including parasites and micropollutants. Their combined effects are hard to predict. This study assessed the trophic relationship, micropollutants bioaccumulation and infection degree in a host-parasite couple. Carbon and nitrogen isotopic ratios were determined in hake Merluccius merluccius muscle and in its parasite Anisakis sp.. Concentrations of both priority (mercury species and polychlorinated biphenyls congeners) and emerging (musks and sunscreens) micropollutants were also measured for the parasite and its host, to detect potential transfer of contaminants between the two species. The results showed partial trophic interaction between the parasite and its host, in accordance with the Anisakis sp. life encysted in hake viscera cavity. PCB transfer between the two species may result from some lipids uptake by the parasite, while no relation occurred for the two other contaminants. Finally, a positive correlation was found between the number of Anisakis sp. larvae and the methylmercury contamination for hake, emphasizing the assumption that the contamination level in methylmercury can weaken immune system of the host enough to affect parasite infection degree. Graphical abstract: Image 1 Highlights: Partial trophic interaction between L3 Anisakis sp. larvae and its host, hake. PCB transfer may result from the uptake of lipids from hake by the parasites. Highly MeHg level in hake can weaken immune system and increase Anisakis sp. number. Abstract : Micropollutant concentrations in hake and its parasite reveal a partial trophic interaction and a link between hake contamination and infection degree by parasites.